Creative Strategies and Tactics for Their Realisation - Andreev, Rumen (Research Papers, 2018)
In the modern world, information is increasing, which complicates decision-making and the adherence to long-term goals. The purpose of the article is to prove that it is now more difficult to build a strategy and that for the imposing of successful strategies are needed more firmness and perseverance. Different conceptions of behavioural economics and cognitive psychology have been used for the study. An interdisciplinary approach was used as investigations of psychology, and neuroeconomics had been combined and analysed.